New Historicism: Text and Context - Violeta M. Vesić (Etnoantropološki Problemi, 2015)
During most of the twentieth century history was seen as a phenomenon outside of literature that guaranteed the veracity of literary interpretation. History was unique and it functioned as a basis for reading literary works. During the seventies of the twentieth century there occurred a change of attitude towards history in American literary theory, and there appeared a new theoretical approach which soon became known as New Historicism. Since its inception, New Historicism has been identified with the study of Renaissance and Romanticism, but nowadays it has been increasingly involved in other literary trends. Although there are great differences in the arguments and practices at various representatives of this school, New Historicism has clearly recognizable features and many new historicists will agree with the statement of Walter Cohen that New Historicism, when it appeared in the eighties, represented something quite new in reference to the studies of theory, criticism and history (Cohen 1987, 33). Theoretical connection with Bakhtin, Foucault and Marx is clear, as well as a kind of uneasy tie with deconstruction and the work of Paul de Man. At the center of this approach is a renewed interest in the study of literary works in the light of historical and political circumstances in which they were created. Foucault encouraged readers to begin to move literary texts and to link them with discourses and representations that are not literary, as well as to examine the sociological aspects of the texts in order to take part in the social struggles of today.